Implementation of Levenshtein Distance Algorithm in the Digital Biology Dictionary Search Function - Khalidah Khalidah (Indonesian Journal of Artificial Intelligence and Data Mining, 2021)
Digital biology dictionary is important to develop as it assists biology students, laboratory assistants, and general users in searching for biology terms. Sometimes, users mistype the biological terms in Latin on the term search form in the biology dictionary. Thus, it is important to implement the Levenshtein distance algorithm to provide query suggestion information to users. This study aims to implement the Levenshtein distance algorithm in the digital biology dictionary search function. This research consists of several stages, namely the development of a search module on the digital biology dictionary, implementation of the Levenshtein Distance algorithm, query suggestion validation. The levenshtein distance algorithm had been successfully implemented in the digital biology dictionary by providing query suggestion output for mistyping words. The results of this study indicate that the system was able to evaluate words with the query suggestion function with an accuracy value of 90%.